Effective Algorithm to Find The Frequency Item Sets Using Datamining. - Pandiammal, R; Kavitha, N (International Journal of Computer Sciences and Engineering, 2025)
Now a day when we transfer the data, we are using private frequency item sets mining algorithm. It has 2 phases that are pre-processing and mining phase. This algorithm is used for utility, privacy and efficiency the frequency item set is planned which is based on frequency pattern growth algorithm. In pre processing phase consists to improve the privacy, utility and novel smart splitting to transpose database. The mining phase consists to offset the information lost during the transformation splitting information and calculate the runtime estimate for actual support of item set in a given data base . Further the dynamic noise reduction technique is used to reduce the noise at the time of mining phase